Effects of low-intensity laser therapy on the stability of orthodontic mini-implants: a randomised controlled clinical trial - Abohabib, Ahmed Mohamed; Fayed, Mona Mohamed Salaheldin; Labib, Amr H. (Taylor & Francis, 2018)
Objective: To investigate the effect of low-intensity laser therapy on mini-implant stability using resonance frequency analysis during canine retraction with fixed appliances. Design: A split-mouth randomised clinical trial. Setting: Subjects were recruited and treated in the outpatient clinic, Department of Orthodontics, Faculty of Dentistry, Cairo University. Participants: Fifteen subjects with mean age 20.9 (±3.4) years who required extraction of maxillary first premolar teeth and mini-implant-supported canine retraction. Methods: Thirty orthodontic mini-implants were inserted bilaterally in the maxillary arches of recruited subjects following alignment and levelling. Mini-implants were immediately loaded with a force of 150 g using nickel titanium coil springs with split-mouth randomisation to a low-intensity laser-treated side and control side. The experimental sides were exposed to low-intensity laser therapy from a diode laser with a wavelength of 940 nm at (0, 7, 14, 21 days) after mini-implant placement. Mini-implant stability was measured using resonance frequency analysis at (0, 1, 2, 3, 4, 6, 8, 10 weeks) after implant placement. Results: A total sample of 28 mini-implants were investigated with 14 in each group. Clinically, both mini-implant groups had the same overall success rate of 78.5%. There were no significant differences in resonance frequency scores between low-intensity laser and control sides from baseline to week 2. However, from week 3 to 10, the low-intensity laser sides showed significantly increased mean resonance frequency values compared to control (P > 0.05). Conclusions: Despite evidence of some significant differences in resonance frequency between mini-implants exposed to low-intensity laser light over a 10 weeks period there were no differences in mini-implant stability. Low-intensity laser light cannot be recommended as a clinically useful adjunct to promoting mini-implant stability during canine retraction.